Osimertinib in patients with advanced epidermal growth factor receptor T790M mutation-positive non-small cell lung cancer: rationale, evidence and place in therapy. (June 2017) - Ricciuti, Biagio; Baglivo, Sara; Paglialunga, Luca; De Giglio, Andrea; Bellezza, Guido; Chiari, Rita; Crinò, Lucio; Metro, Giulio
The identification of epidermal growth factor receptor ( EGFR ) mutations represented a fundamental step forward in the treatment of advanced non-small cell lung cancer (NSCLC) as they define a subset of patients who benefit from the administration of specifically designed targeted therapies. The inhibition of mutant EGFR through EGFR -tyrosine kinase inhibitors (TKIs), either reversible, first-generation gefitinib and erlotinib, or irreversible, second-generation afatinib, has dramatically improved the prognosis of patients harboring this specific genetic alteration, leading to unexpected clinical benefit. Unfortunately, virtually all patients who initially respond to treatment develop acquired resistance to EGFR -TKIs within 9–14 months. The EGFR T790M secondary mutation has emerged as a cause of treatment failure in approximately 60% of resistant cases. To date, several compounds designed with the aim to overcome T790M-mediated resistance are under clinical investigation. The aim of this review is to discuss emerging data regarding the third-generation EGFR -TKI, osimertinib, for the treatment of EGFR T790M mutant advanced NSCLC.